MENINGKATKAN KEPUASAN KERJA: PERAN BUDAYA ORGANISASI, LINGKUNGAN KERJA, DAN PERCEIVED ORGANIZATIONAL SUPPORT - Ignatius Soni Kurniawan (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2021)
This study aims to determine the effect of organizational culture, work environment, and perceived organizational support on job satisfaction. The population used in this study were employees of PT Grand Puri Persada Yogyakarta, the sampling technique used in this study was non probality sampling, with saturated samples. Data were taken using a questionnaire on 50 respondents and processed using multiple linear regression analysis. The results in this study state that organizational culture, work environment, and perceived organizational support have a positive and significant effect on job satisfaction. The findings imply that company leaders can encourage increased job satisfaction through evaluation of items from organizational culture, work environment, and perceived organizational support which are still low which have been mentioned in the discussion section.